Analisis Krisis Komunikasi dalam Konflik Pengurus Besar Nahdlatul Ulama versus Partai Kebangkitan Bangsa - Alamsyah, Alamsyah; Misnan, Misnan; Sukma, Agus Hitopa; Pranawukir, Iswahyu (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study examines the communication crisis in the conflict between the Nahdlatul Ulama Executive Board (PBNU) and the National Awakening Party (PKB) using Fairclough’s Critical Discourse Analysis (CDA) approach. The research object consists of the message constructions of each party as represented in mainstream media publications and official releases, including the Vice President’s statement (01 August 2024, wapresri.go.id), Kompas articles (07 and 25 August 2024), and detikBali (11 August 2024). These secondary data sources were analyzed to understand how PBNU and PKB shape, assert, and maintain their respective discourses during the escalation of the conflict. The analysis reveals that PBNU frames its messages through a moral–cultural lens, emphasizing the organization’s role in safeguarding religious values and positioning the conflict as an internal matter requiring rectification. Conversely, PKB employs a political legitimacy frame, asserting the party’s independence, rejecting external intervention, and emphasizing a professional political agenda. The divergence in message constructions generates communication asynchrony, potentially reinforcing organizational polarization and public perception disparities. The study underscores that critical discourse analysis of media publications offers profound insights into inter-institutional communication crises and highlights the importance of strategic message management in mitigating conflict.